When Values Matter: Middle Managers’ Behavior and Knowledge Hiding in Public Organizations - Ingrida Girnienė; Neringa Mikėnaitė; Zenona Ona Atkočiūnienė (European Conference on Knowledge Management, 2026)
In recent years, public sector organizations have faced increasing pressure not only to ensure transparency, accountability and service to society, but also to respond effectively to rapidly changing environments. Achieving these expectations depends not solely on formal regulations and procedures, but also on how knowledge is created, shared and used within organizations. Knowledge hiding – defined as the intentional concealment of requested knowledge, poses a significant barrier to organizational learning, effective decision-making, and public trust. While prior research has examined individual and contextual antecedents of knowledge hiding, less attention has been given to the role of middle managers’ value-based behaviour in shaping everyday knowledge practices in public organizations. This study examines the role of middle managers’ value-based behaviour in reducing knowledge hiding in public organizations. Drawing on a case study conducted within a public-sector organization, the study adopts a mixed-methods approach. The present paper reports findings from the first, qualitative stage of the study, based on semi-structured interviews with middle managers, exploring their perceptions of how managerial behaviour relates to knowledge-hiding practices. The findings suggest that, according to the interviewed managers, employees were less inclined to engage in knowledge hiding when immediate managers were seen as acting in accordance with the organization’s declared values. Managers also described trust and psychological safety as important relational conditions associated with both values-based managerial behaviour and knowledge-sharing practices. The interviews further suggest that value alignment between employees and the organization may strengthen the perceived role of values-based managerial behaviour in fostering psychological safety, although managers noted that this relationship depends on organizational context. The study contributes to knowledge management research by positioning value-based behaviour of middle managers as an important contextual factor that managers perceive as influencing knowledge-hiding practices in public organizations. The findings offer practical insights for fostering trust-based and psychologically safe environments that support more open and cooperative knowledge practices in the public sector.